Thoracic Aortic Aneurysm from Chronic Antiestrogen Therapy - Tripathi, Rishi; Sainathan, Sandeep; Ziganshin, Bulat A.; Elefteriades, John A. (International Journal of Angiology, 2017)
Aortic aneurysms are a common but often undetected pathology prevalent in the population. They are often detected as incidental findings on imaging studies performed for unrelated pathologies. Estrogens have been shown to exert a protective influence on aortic tissue. Pharmacological agents blocking the actions of estrogens may thus be implicated in causing aortic pathologies. We present the case of an elderly woman with breast carcinoma treated for 18 years with antiestrogen therapy who subsequently developed acute thoracic aortic deterioration (enlargement and wall disruption).
Keywords: aortic aneurysm; estrogen; breast carcinoma